Diabetes type 2 diabetes in the elderly – solved and unsolved questions - Tat'jana Vladimirovna Saprina; Nailja Maratovna Fajzulina (Сахарный диабет)
The number of elderly persons with diabetes mellitus type 2 is expected to progressively increase. Management of this category of patients should be individualised and include the adequate correction of hyperglycaemia, prevention of long-term complications, prevention of hypoglycaemia, reduction of cardiovascular mortality and preservation of quality of life. This article summarises basic information on the pathophysiology of carbohydrate metabolism, peculiarities of the course of diabetes and use of antidiabetic drugs in the elderly. Special attention is paid to reviewing the goals of glycaemic control and proposed clinical guidelines.